The Role of HR in Promoting Diversity, Equity, and Inclusion in the Workplace - Radha, P; Neupane, Dasarath; Sayyed, Nasreen (NPRC Journal of Multidisciplinary Research, 2025)
Background: In the contemporary globalized business environment, Diversity, Equity, and Inclusion (DEI) have transitioned from a moral imperative to a strategic advantage. Human Resources (HR) is pivotal in driving DEI initiatives, responsible for embedding these principles into core organizational functions such as recruitment, training, performance management, and policy development to foster an inclusive culture where all employees can thrive.Objective: This study aims to (1) examine the role of HR in developing and implementing DEI policies and practices, and (2) evaluate the impact of these HR-driven DEI initiatives on employee satisfaction, organizational culture, and overall business performance.Methods: A mixed-methods approach was employed, combining quantitative and qualitative techniques. The quantitative component involved a survey of 240 HR professionals and employees to assess the perceived effectiveness of various DEI initiatives (recruitment, training, performance evaluation, employee engagement), analyzed using Chi-Square and ANOVA tests. The qualitative component consisted of in-depth interviews with HR managers and diversity officers to gain insights into challenges and best practices.Findings: The Chi-Square test revealed a statistically significant association between HR practices and the perceived effectiveness of DEI initiatives (χ² = 8.89, p < 0.05), with recruitment and employee engagement practices being perceived as most effective. Conversely, the ANOVA test indicated no significant difference in employee satisfaction levels across the different types of DEI initiatives (F = 2.36, p > 0.05).Conclusion: HR plays a critical role in the perceived effectiveness of DEI initiatives. However, the consistent level of employee satisfaction across all initiative types suggests that while HR practices are influential, a more tailored and strategic approach is required to significantly enhance satisfaction and other business outcomes.Implication: The findings imply that organizations should move beyond standardized DEI programs. HR departments are advised to customize strategies based on employee feedback, enhance inclusive recruitment with technology, promote inclusive leadership, implement continuous training, and strengthen accountability through DEI-specific KPIs to build a truly equitable and high-performing workplace.